A novel PTEN gene promoter mutation and untypical Cowden syndrome - Liu, Chen; Li, Guangbing; Chen, Rongrong; Yang, Xiaobo; Zhao, Xue; Zhao, Haitao (Chinese Journal of Cancer Research; Vol 25, No 3 (June 28, 2013): Chinese Journal of Cancer Research, 2013)
Cowden syndrome (CS), an autosomal dominant disorder, is one of a spectrum of clinical disorders that have been linked to germline mutations in the phosphatase and tensin homolog (PTEN) gene. Although 70-80% of patients with CS have an identifiable germline PTEN mutation, the clinical diagnosis presents many challenges because of the phenotypic and genotypic variations. In the present study, we sequenced the exons and the promoter of PTEN gene, mutations and variations in the promoter and exons were identified, and a PTEN protein expression negative region was determined by immunohistochemistry (IHC). In conclusion, a novel promoter mutation we found in PTEN gene may turn off PTEN protein expression occasionally, leading to the disorder of PTEN and untypical CS manifestations.